Sustainability of Austrian public debt: a political economy - Gottfried Haber; Reinhard Neck (Center for Economic Studies and ifo Institute (CESifo), 2006)
Sustainablity of Austrian public debt is investigated in the context of political objectives such as stabilizing the business cycle, increasing chances for being re-elected and implementing the ideologies of political parties. Several tests indicate that Austrian fiscal policies were sustainable in the period 19601974, while from 1975 on, public debt grew much more rapidly. The development of public debt in Austria seems to be driven not primarily by ideology, but by structural causes and a shift in the budgetary policy paradigm. We find some empirical evidence that governments in Austria dominated by one party run higher deficits than coalition governments. There are no indications of a political business cycle.
Keywords: H6; E6; 330; Finanzpolitik; Nachhaltige Entwicklung; Öffentliche Schulden; Zeitreihenanalyse; Österreich